The social determinants of oral health: new approaches to conceptualizing and researching complex causal networks - Newton JT, Bower EJ. (Blackwell Synergy, 2005)
Oral epidemiological research into the social determinants of oral health has been limited by the absence of a theoretical framework which reflects the complexity of real life social processes and the network of causal pathways between social structure and oral health and disease.